Quantification of mono-, di-, tri-chlorinated biphenyl in Ganga River: design of experiment, source analysis and spatial distribution - Sandeep Kumar; Triparna Das; Anshul Tiwari; Pranjal Yadav; Zain Ali; Jorge Paz-Ferreiro; Devendra Kumar Patel (Discover Water)
Abstract Low-chlorinated polychlorinated biphenyls (LC-PCBs) pose a significant environmental threat to river systems due to their higher volatility, mobility, and solubility compared to higher chlorinated PCBs (HC-PCBs). This study aimed to detect and quantify mono-, di-, and tri-chlorinated PCB congeners in the Ganga River, focusing on sections in Kanpur, an industrial hub, and Prayagraj, known for religious activities. We developed and optimized a liquid–liquid microextraction method using hexane as a solvent. The extraction parameters were optimized using Central Composite Design (CCD), confirming a significant quadratic model fit (p < 0.0001) with a R2 of 0.9262, achieving optimal extraction efficiency. The method demonstrated limits of detection (LOD) ranging from 0.04 to 2.1 µg L−1, limits of quantification (LOQ) from 0.1 to 6.5 µg L−1, and recovery rates between 73.3 and 106.7%. The expanded uncertainty (%) ranged between 2.4 to 4.0%. Analysis of water samples from Kanpur (K1–K11) and Prayagraj (P1–P11) revealed significantly higher LC-PCB contamination in Kanpur. Principal component analysis (PCA) indicated that industrial activities were the primary contributors to the observed pollution, with the first principal component explaining 49% of the variance. Partial least squares discriminant analysis identified PCB-2, PCB-4, PCB-5, and PCB-18 as significant contaminants. Spatial distribution mapping highlighted K10 (Kanpur) and P1 (Prayagraj) as critical hotspots, suggesting localized point-source contamination. This study provides a robust analytical framework for the detection and quantification of LC-PCBs in aquatic environments. The findings underscore the impact of industrialization on LC-PCB pollution in the Ganga River and highlight the need for targeted environmental interventions to mitigate contamination and protect ecosystem and public health.